2020
DOI: 10.1111/1462-2920.15082
|View full text |Cite
|
Sign up to set email alerts
|

Culturomics‐based genomics sheds light on the ecology of the new haloarchaeal genus Halosegnis

Abstract: The development of culture-independent techniques has revolutionized our understanding of microbial ecology, especially through the illustration of the vast gap between the environmentally abundant microbial diversity and that accessible through cultivation. However, culture-based approaches are not only crucial for understanding the evolutionary, metabolic and ecological milieu of microbial diversity but also for the development of novel biotechnological applications. In this study, we used a culturomics-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 107 publications
3
19
0
Order By: Relevance
“…Thus, the biosynthesis of this wide variety of secondary metabolites by strains of the genus Halomicroarcula suggests the versatility of members of this genus, which have developed several ecological advantages such as a great adaptability to extreme conditions or defense mechanisms. In addition, our results brought to light their possible applications on the biotechnological field as a source of new natural compounds, also recently proposed for other novel haloarchaeal taxa (Durán-Viseras et al, 2021).…”
Section: Biosynthesis Of Secondary Metabolitesmentioning
confidence: 60%
See 3 more Smart Citations
“…Thus, the biosynthesis of this wide variety of secondary metabolites by strains of the genus Halomicroarcula suggests the versatility of members of this genus, which have developed several ecological advantages such as a great adaptability to extreme conditions or defense mechanisms. In addition, our results brought to light their possible applications on the biotechnological field as a source of new natural compounds, also recently proposed for other novel haloarchaeal taxa (Durán-Viseras et al, 2021).…”
Section: Biosynthesis Of Secondary Metabolitesmentioning
confidence: 60%
“…Previous metagenomic studies on prokaryotic diversity of hypersaline soils showed a large proportion of haloarchaea, with a high percentage not closely related to any previously described taxa. For that reason, we isolated a large collection of strains from the Odiel saltmarsh hypersaline soils located in Huelva, South-west Spain, using different complex oligotrophic media and culture conditions, based on culturomics techniques as previously detailed ( Durán-Viseras et al, 2021 ). Partial sequencing of the 16S rRNA gene permitted us to preliminary delineate the taxonomic position of the isolates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent successes with cultivating Candidatus Nanohaloarchaeota as co-cultures with Halobacteria opens up an exciting new hot spot in the field of halophilic archaea research. It is anticipated that improvements in cultivation technology (also termed 'culturomics' (Durán-Viseras et al 2020;Greub 2012), such as the use of robotics and highthroughput microchambers (Nichols et al 2010) will greatly increase the ability to cultivate diverse halophilic archaea from different hypersaline environments, so that many thousands of isolates can be recovered and analyzed simultaneously (Berdy et al 2017).…”
Section: Future Perspectivesmentioning
confidence: 99%